Cutibacterium acnes dysbiosis: Alternative therapeutics for clinical application - Sá, Sara (2023)
Cutibacterium acnes (C. acnes) is a Gram-positive anaerobic facultative bacterium that is part of the human skin commensal microbiome. It colonizes various regions of the body, including the face, back, and chest. While typically a harmless commensal, under certain conditions, C. acnes can become pathogenic, leading to or promoting conditions such as acne vulgaris (AV), post-surgical infections, prostate cancer, and sarcoidosis. Current treatments for C. acnes infections often involve antibiotics, but the rise of antibiotic resistance has raised concerns. This review presents the virulence factors, clinical relevance, and current treatments of C. acnes, highlighting its association with AV, postsurgical infections, and other diseases. It also explores alternative innovative therapies such as phage therapy in development/research that are gaining prominence, with a growing focus on personalized medical approaches. To enhance C. acnes treatment while minimizing side effects and antibiotic prescription concerns, numerous clinical studies have been undertaken. These investigations span various pathological profiles and employ diverse strategies, such as utilizing bacterial extracts and compounds to restore healthy skin flora. The limitations and challenges of current and innovative treatments are also addressed, emphasizing the need for multidisciplinary strategies to combat C. acnes infections effectively.